학습 플랫폼을 활용한 고등학생의 수학 교수·학습 사례 연구 - 정은영; 김형원; 고호경 (East Asian Mathematical Journal, 2022)
Recently, various platforms of education technology (Edu-Tech) that use artificial intelligence have been developed in the field of mathematics education. The case study in this paper reports the learning experience of a high school student who was directed to learn mathematics through the self-directed learning process provided by a mathematics learning platform using Edu-Tech with the intervention of mentoring provided by his teacher. The study found that the mentoring intervention could make an effective contribution to student’s mathematics learning by playing the role of an auxiliary tool for the self-directed learning over time. In this paper, we explain the nature of the challenges that the student encountered in the process of self-directed learning and the roles that the teacher mentoring has played in this process.
Keywords: math learning platform; Edu-Tech; mentoring